1997
DOI: 10.1046/j.1365-2141.1997.3123128.x
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells generated from the blood of patients with multiple myeloma are phenotypically and functionally identical to those similarly produced from healthy donors

Abstract: Summary. Using a combination of GM-CSF, SCF, flk-2/flt-3 ligand, and IL-4, dendritic cells (DC) have been generated in vitro from the adherent fraction of mononuclear cells isolated from the blood of patients with MM. Analysis of cell yield showed no significant difference in DC yield (numbers or percentage of leucocytes) or total number of leucocytes generated in myeloma cultures compared to similar cultures prepared using mononuclear cells from the blood of healthy donors. The mean number of DC produced afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Accordingly, while some studies have shown the presence of lower numbers of circulating mDCs [35] or both mDCs and pDCs in MM patients [21], others did not find significant differences with regard to healthy individuals [22,28,29]. In the present study, we found lower absolute and relative numbers of mDCs in MM patients but not in MGUS patients, together with greater numbers of all subsets of PB DCs in PCL patients.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Accordingly, while some studies have shown the presence of lower numbers of circulating mDCs [35] or both mDCs and pDCs in MM patients [21], others did not find significant differences with regard to healthy individuals [22,28,29]. In the present study, we found lower absolute and relative numbers of mDCs in MM patients but not in MGUS patients, together with greater numbers of all subsets of PB DCs in PCL patients.…”
Section: Discussionsupporting
confidence: 47%
“…Accordingly, while some studies found no alterations in MM DCs from these patients [28,29], others have reported lower expression levels of HLA-DR, CD40, and CD80, together with a lower antigen-presenting capacity and failure to upregulate CD80 expression [21,22]. Some of these discrepancies could be a result, at least to a certain extent, of either the different subpopulations of DCs analyzed after in vitro culture or the distinct technical approaches employed [21,22,28,29].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…10,14 Conversely, DCs generated in vitro from monocyte precursors are capable of efficient T-cell stimulation. 17,24,26,27 These studies suggest that circulating PBDCs may not be optimal vehicles for antigen delivery in immunotherapy trials of cancer. The inhibitory effect of IL-6 was abrogated by anti-IL-6 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency, phenotype, and function of these cells have been described to be altered by some authors and normal by others. Moreover, different protocols of DC purification and maturation and different ways of measuring DC activity have produced data [20][21][22][23][24][25][26] that cannot be compared and that do not often include MGUS patients.…”
Section: Discussionmentioning
confidence: 99%